Strategi Pro-Growth Dalam Pengembangan Pantai Klayar Sebagai Destinasi Pariwisata Unggulan Kabupaten Pacitan (Studi Pada Dinas Kebudayaan, Pariwisata, Pemuda dan Olahraga Kabupaten Pacitan) - Damayanti, Aprelia Dyah (Jurnal Administrasi Publik, 2014)
Abstract: Pro-Growth Strategy For The Development of Klayar Beach as the Pre-eminent Tourism Destinations in Pacitan District (Study in the Department Of Culture, Tourism, Youth and Sport Pacitan District). Pro-growth strategy is one of the strategies used in the development of tourism in Indonesia, both at central and local. Including the development of tourism in Pacitan District especially for Klayar Beach that has the potensial to be a leading tourism destination.. To determine the pro-growth strategy in the development of Klayar Beach used descriptive research with the mixed approach. With the interactive model analysis of Miles and Huberman, IE (Internal External) matrix analysis and SWOT analysis. Based on analysis of interactive models is known that the pro-growth strategy in the development of Klayar Beach through ecotourism, improved infrastructure, increased promotion and marketing, increased collaboration with the private sector, and increased society participation. IE matrix produces a general strategy through increased facilities, products, tourism technologies and joint ventrure. SWOT matrix produce an alternative strategy that is strategies (SO) product development and tourist attraction, strategies (WO) infrastructure development and promotion, strategies (ST) suistainable tourism development, and strategies (WT) of human resources development and coordination between sectors. Keywords: development, strategy, tourism and Klayar Beach Abstrak: Strategi Pro-Growth dalam Pengembangan Pantai Klayar Sebagai Destinasi Pariwisata Unggulan Kabupaten Pacitan (Studi Pada Dinas Kebudayaan, Pariwisata, Pemuda dan Olahraga Kabupaten Pacitan). Strategi Pro-growth adalah salah satu strategi yang digunakan dalam pengembangan pariwisata di Indonesia baik di tingkat pusat maupun daerah. Termasuk pengembangan pariwisata di Kabupaten Pacitan terutama untuk Pantai Klayar yang memiliki potensi menjadi destinasi pariwisata unggulan. Untuk mengetahui strategi pro-growth dalam pengembangan Pantai Klayar digunakan jenis penelitian deskriptif dengan pendekatan gabungan. Dengan analisis model interaktif Miles and Huberman, analisis matriks IE (Internal Eksternal) dan analisis SWOT. Berdasarkan hasil analisis model interaktif diketahui bahwa strategi pro-growth dalam pengembangan Pantai Klayar melalui ekowisata, peningkatan sarana prasarana, peningkatan promosi dan pemasaran, peningkatan kerjasama dengan swasta, dan peningkatan partisipasi masyarakat. Matriks IE menghasilkan strategi umum melalui peningkatan fasilitas, produk dan teknologi pariwisata serta joint ventrure. Matriks SWOT menghasilkan strategi alternatif yaitu Strategi (SO) pengembangan produk dan daya tarik wisata, strategi (WO) pengembangan sarana prasarana dan promosi, strategi (ST) pengembangan pariwisata berkelanjutan, dan strategi (WT) pengembangan SDM dan koordinasi antar sektor. Kata Kunci: pengembangan, strategi, pariwisata dan Pantai Klayar